Guidelines of guidelines: a review of urethral stricture evaluation, management, and follow-up - Bayne, David B.; Gaither, Thomas W.; Awad, Mohannad A.; Murphy, Gregory P.; Osterberg, E. Charles; Breyer, Benjamin N. (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Background: Our objective is to report a comparative review of recently released guidelines for the evaluation, management, and follow-up of urethral stricture disease. Methods: This is an analysis of the American Urologic Association (AUA) and Société Internationale d’Urologie (SIU) guidelines on urethral stricture. Strength of recommendations is stratified according to letter grade that corresponds to the level of evidence provided by the literature. Results: Although few, the discrepancies between the recommendations offered by the two guidelines can be best explained by varying interpretations of the literature and available evidence on urethral strictures. When comparing the AUA guidelines and the SIU guidelines on urethral stricture, there are very few discrepancies. Perhaps the most notable difference is in the use of repeat DVIU or urethral dilation after an initial failed attempt. SIU guidelines state that there are instances where repeat DVIU or urethral dilation can be indicated, and they give a range of time at which stricture recurrence post procedure mandates an urethroplasty (less than 3 to 6 months). The AUA guidelines definitively state that repeat endoscopic procedures should not be offered as an alternative to urethroplasty, and they do not mention time of stricture recurrence as a factor. SIU guidelines allow for management of urethral stricture with indwelling urethral stenting. Conclusions: Overall there is a need for more high quality research in the work up, management, and follow up care of urethral stricture.